CENELEC 50128 and IEC 62279 Standards. - Boulanger, Jean-Louis (Control, systems and industrial engineering series., 2015)
CENELEC EN 50128 and IEC 62279 standards are applicable to the performance of software in the railway sector. The 2011 version of the 50128 standard firms up the techniques and methods to be implemented. This is a guide to its implementation, in order to understand the foundations of the standard and how it impacts on the activities to be undertaken, helping towards better a preparation for the independent evaluation phase, which is mandatory.